PROBLEMATIC APPLICATION OF CRIMINAL REVOCATION OF POLITICAL RIGHTS IN PERSPECTIVE OF CORRUPTION LAW - Edi As' Edi (Jurnal Dinamika Hukum, 2015)
The spirit of fighting corruption in Indonesia based on the spirit of the Declaration of the 8th International Conference against Corruption and Indonesia United Nations Convention against Corruption (UNCAC) UN 58/ 4 dated October 31, 2003, and Law No. 7 of 2006 on the Ratification of the UN Convention on Anti-Corruption of 2003 and Act No. 20 of 2001. The implementation of the Law on Corruption tends not optimal. As a new breakthrough reached the imposition of criminal sanctions in the form of revocation of political rights for the accused of corruption. Although in practice the criminal is considered unconstitutional. Given the enormous impact of corruption, namely the loss suffered by the people and the state, the current criminal disenfranchisement for perpetrators of political corruption has been duly applied. Keywords: pull, rights, corruption, politics.